(untitled) (Journal of Pathology of Nepal, 2020)
Most of the oral ulcers are traumatic in origin due to sharp tooth and self bite. Traumatic ulcerative granuloma with stromal eosinophilia is a chronic benign lesion of the oral mucosa with uncertain histogenesis. Trauma was proposed to be an inciting factor. A series of four cases of Traumatic Ulcerative Granuloma with Stromal Eosinophilia in the lateral borders of the tongue were analyzed regarding oral hygiene, sharp tooth, clinical presentation, histology, and follow-up. The lesion manifests as a small solitary ulcer with induration in the oral mucosa mimicking malignancy. Histology revealed ulcers with exudate and granulation tissue with dense polymorphous infiltrate rich in eosinophils. Infiltrate extends down in between the skeletal muscle fibers and salivary gland lobules. A sharp tooth was found to be the inciting factor in a proportion of cases. Histopathological examination is mandatory to confirm the diagnosis and to exclude malignancy and other eosinophil rich disorders.